Effects of heat source/sink and chemical reaction on MHD maxwell nanofluid flow over a convectively heated exponentially stretching sheet using homotopy analysis method - Sravanthi, C.S.; Gorla, Rama Subba Reddy (Zielona Góra: Uniwersytet Zielonogórski)
The aim of this paper is to study the effects of chemical reaction and heat source/sink on a steady MHD (magnetohydrodynamic) two-dimensional mixed convective boundary layer flow of a Maxwell nanofluid over a porous exponentially stretching sheet in the presence of suction/blowing. Convective boundary conditions of temperature and nanoparticle concentration are employed in the formulation. Similarity transformations are used to convert the governing partial differential equations into non-linear ordinary differential equations.
Keywords: HAM; chemical reaction; heat source/sink; Maxwell nanofluid; porous exponentially stretching sheet; convective boundary conditions